Is FDG-PET/CT used correctly in the combined approach for nodal staging in NSCLC patients? - Simsek, F. S.; Comak, A.; Asik, M.; Kuslu, D.; Balci, T. A.; Ulutas, H.; Akyol, H. (Wolters Kluwer Medknow Publications, 2020)
Background: The most widely accepted approach nowadays in nodal staging of non-small cell lung cancer (NSCLC) is the combined use of 18-Fluorodeoxyglucose-positron emission tomography/computed tomography (FDG-PET/CT) and endobronchial ultrasound-transbronchial needle aspiration (EBUS-TBNA). However, this approach may not be sufficient, especially for early stages. Aims: Our aim was to assess whether more satisfactory results can be obtained with standardized uptake value maximum lymph node/standardized uptake value mean mediastinal blood pool (SUVmax LN/SUVmean MBP), SUVmax LN/Primary tumor, or a novel cut-off value to SUVmax in this special group. Subjects and Methods: Patients with diagnosed NSCLC and underwent FDG-PET/CT were reviewed retrospectively. 168 LNs of 52 early stage NSCLC patients were evaluated. The LNs identified in surgery/pathology reports were found in the FDG-PET/CT images. Anatomic and metabolic parameters were measured. Statistical analysis was performed by using of MedCalc Statistical Software. Results: Regardless of LNs size; sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of SUVmax >2.5 were 91.5%, 65.9%, 58.2%, and 95.1%, respectively. Optimum cut-off value of SUVmax was >4.0. Sensitivity, specificity, PPV, and NPV were found as 81.0%, 90.0%, 81.0%, and 90.0% respectively. Optimum cut-off value of SUVmax LN/SUVmean MBP was >1.71. Sensitivity, specificity, PPV, and NPV were found as 94.7%, 80.0%, 71.1%, and 96.7%, respectively. Optimum cut-off value of SUVmax LN/Primary tumor was >0.28. Sensitivity, specificity, PPV, and NPV were found as 81.1%, 85.1%, 72.9% and 90.1%, respectively. Conclusion: SUVmax LN/SUVmean MBP >1.71 has higher PPV than currently used, with similar NPV and sensitivity. This can provide increase in the accuracy of combined approach. In this way, faster nodal staging/treatment decisions, cost savings for healthcare system and time saving of medical professionals can be obtained.
Keywords: EBUS-TBNA; FDG-PET; CT; NSCLC; staging